DOUBLE STANDARDS IN ECONOMIC POLICY AND THE SHADOW ECONOMY - S. Chernov (Вестник университета)
Arguments justifying the necessity to study reasons of double standards in economic policy have been presented. The causes of double standards have been considered and systematized. The modern treatment of shadow lobbying has been given. The connection between double standards and development of shadow economy and corruption has been ascertained. The functions of state in the field of opposition of double standards have been discussed.